Information and Communication Technology Utilization for Managerial Planning Among Educational Administrators in Secondary Schools in Ilorin Metropolis - Olalekan BOLAJI, Hammed; BOLAJI, Tajudeen Oluwafemi (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2022)
This study examines how secondary school administrators in the Ilorin Metropolis use ICT for managerial planning. The principal must effectively and efficiently organize, manage, and supervise the school's business for them to run successfully. This study's design is a survey-style descriptive study to determine how ICT affects principals' administrative performance. The population of this study consisted of 292 participants from all 75 public secondary schools in the Ilorin Metropolis. The instrument for data collection was a structured questionnaire titled "Information Communication Technology and Principal's Administrative Effectiveness Questionnaire" (ICTPAEQ) while reliability coefficient values of 0.85 were obtained. The data gathered from the field was evaluated using pertinent descriptive statistics such as percentages, mean, and standard deviation, while research question 4 was addressed using Pearson Production Moment Correlation (PPMC) statistics. This finding may be explained by the fact that most schools lacked these ICT resources, which may have contributed to the finding. This finding revealed that secondary school principals do better administratively the more they use ICT resources. This further implies that secondary school management effectiveness may be in danger in the absence of ICT. This implied that ICT is a crucial factor in the efficient administration of secondary schools. Based on the findings of this study, the following recommendations were made for secondary school administrators to become more proficient and use ICT technologies to enhance training for school administrators who are not yet ICT proficient.